Situated learning theory and incubatee performance at the DOST technology business incubator program: Is entrepreneurial learning and development a mediator? - Que, James Charles T. (Animo Repository, 2022)
Incubatee startup founders asks for solutions and ideas whenever they encountered business problems in their startups enrolled in a Technology Business Incubator program. It is argued that situated learning may help these incubatees find solutions to their problems via interaction with co-incubatees. Some incubatees who have previous working experience do have a certain level of entrepreneurial learning that contributes to their performance. To test, 58 incubatees were surveyed on the mediating effect of entrepreneurial learning and development on the hypothesized situated learning – incubate performance nexus. Incubator managers from different TBIs were invited to cross validate the survey results through written narratives. Mediation analysis disclosed that situated learning and entrepreneurial learning and development significantly affected incubatee performance although both variables are poor predictors if taken altogether. Entrepreneurial learning and development attained by the incubatees does not mediate the link between situated learning and incubatee performance. Insights from the written narratives of the interviewees have corroborated with the results. Recommendation given from the study is to pursue a study using other frameworks in order to understand further what may play a critical role in incubatee performance.